Valor prognóstico de marcadores imuno-histoquímicos e variáveis histomorfológicas em mastocitomas cutâneos caninos - Gundim, Lígia Fernandes (2022)
Mast cell tumors are one of the most common tumors in dogs. Due to the variable behavior of this neoplasm, the investigation of prognostic factors that can help in predicting the behavior of these tumors is essential. The objective was to evaluate: histomorphological alterations in canine mast cell tumors, the immunohistochemical expression of c-KIT and Ki-67, the expression of AgNOR, the correlation between these variables and their influence on the clinical evolution of dogs with mast cell tumors, as well as epidemiological characteristics and clinics of the tumor and its relationship with the death of the animal. In the chi-square test, there was a relationship between architecture and degree according to Kiupel (p= 2.907-6), mitosis and degree according to Patnaik (p=0.003). SRD animals had more grade II neoplasms (p=0.045), and animal death was related to tumor ulceration (p=0.006) and animal age (p=0.001). In the correlation matrix, there was an association between the number of eosinophils and tumor extension (p=0.221) and architecture (0.338); architecture and number of mitoses (0.339); bleeding and grading according to Patnaik (p=0.190). In the log-rank test, architecture (p=0.006), number of mitoses (p=0.000), Patnaik grading (p=0.045) and Kiupel grading (p=0.000), AgNORs count (p=0, 39), Ki67 (p=0.03), Ag67 index (p=0.06) and KIT pattern (p=0.17), influenced the survival of the animals. It was concluded that tumor ulceration, architecture, number of mitoses, histological grading, Ki67, Ag67 index and KIT pattern can be used as prognostic factors for mast cell tumors in dogs.